2016
DOI: 10.1111/crj.12471
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of exhaled nitric oxide in patients with lung cancer

Abstract: Introduction and Objectives: To investigate the clinical value of fractional exhaled nitric oxide (FeNO) in lung cancer patients. Methods: A total of 172 healthy control subjects and 164 patients with histopathologically confirmed lung cancer were enrolled in this study. The FeNO measurements and pulmonary function tests were conducted in the Chinese PLA General Hospital. The recorded data included FeNO, the forced expiratory volume in one second (FEV 1 ), the forced vital capacity (FVC), FEV 1 /FVC, the FEV 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
1
25
0
2
Order By: Relevance
“…The intrinsic factors include tumor suppressor proteins, oncoproteins, and epigenetic regulators, whereas the extrinsic factors include microenvironmental mediators, cytokines, and paracrines in the circulating system. NO is a microenvironmental mediator that is elevated in several types of cancer, including lung cancer, colon cancer, and breast cancer (19,59,60). An aberrantly high expression of NO was also shown to be correlated with poor prognosis of several cancers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The intrinsic factors include tumor suppressor proteins, oncoproteins, and epigenetic regulators, whereas the extrinsic factors include microenvironmental mediators, cytokines, and paracrines in the circulating system. NO is a microenvironmental mediator that is elevated in several types of cancer, including lung cancer, colon cancer, and breast cancer (19,59,60). An aberrantly high expression of NO was also shown to be correlated with poor prognosis of several cancers.…”
Section: Discussionmentioning
confidence: 99%
“…As Oct4 (72)(73)(74) and Cav-1 (75)(76)(77)(78) were found in various types of normal and cancerous cells, and the function of Oct4 in the regulation of stem cell properties was widely demonstrated in both CSC and noncancerous stem cells (72)(73)(74), it is interesting to investigate for the Cav-1:Oct4 suppressor complex in normal stem cells. Also, the abundance of Oct4 in cancer cells may be enhanced by the fact that the cancer cells frequently reside in a high NO concentration environment (19) or gain of Akt function (79).…”
Section: Nitric Oxide Maintains Oct4 By Dissociating Caveolin-1mentioning
confidence: 99%
See 2 more Smart Citations
“…After at least 28 years of exploration, it was determined that the detection of FeNO could accurately predict lung cancer, asthma, scleroderma, sarcoidosis and other lung diseases [5][6][7][9][10][11][12][13][14][15][16][17] . After the severe acute respiratory syndrome coronavirus (SARS-CoV) outbreak in 2002-2003, relevant studies showed that the NO concentration in the organism changes with the degree of infection by a coronavirus 18,19 . For example, in the early stage of infection with SARS-CoV, activation of epithelial cells, such as those in alveoli, to produce cytokines results in the upregulation of inducible NO synthase, further increasing the NO concentration and thus playing an antiviral role in controlling SARS-CoV infection 20 .…”
mentioning
confidence: 99%